The Design Process for Entrapping Limonin and Naringin in Siam Juice by Cyclodextrin - Dian Fajarika; Erliza Noor (IPTEK Journal of Proceedings Series, 2014)
Siam juice contain limonin and naringin that produce a bitter taste although these compounds useful  as an antioxidant and anticancer. Bitter taste in juice is unfavor for consumer. The purpose of this research was to find the best conditions in reducing bitter taste in Siam juice by using cyclodextrin and cellulose acetate. These research performed at variation of mixing temperature  (27; 60 and 80ºC), cyclodextrin concentration (0.1; 0.3 and 0.5% (w/v)) and cellulose acetate ( 0.2; 0.4 and 0.6% (w / v)). The results showed that the use of cyclodextrin and cellulose acetate were able to trap limonin and naringin. The higher reducing limonin juice was 91.57% by addition cyclodextrin 0.1% at 60ºC, whereas for naringin obtain by addition cellulose acetate 0.5% at 79.69% . At this temperature, the juice quality (vitamin C) can be maintained.